Prometheus unbound: Unravelling the underlying nature of disputes - Love, Peter; Davis, Peter; Ellis, J.; Evans, Philip (RICS, 2009)
Research has revealed that factors such as scope changes, poor contract documentation, restricted access, unforeseen ground conditions and contractual ambiguities are contributors of disputes. While this is widely known, disputes still prevail over such issues. Before disputes can be avoided an understanding of the pathogens that contribute to their occurrence needs to be determined so that mechanisms can be put in place to prevent them from arising. To determine the pathogens contributing to disputes, a total of 41 in-depth interviews were undertaken with industry practitioners who identified 58 examples of disputes in projects that they have been actively involved with. Analysis of the findings revealed that the pathogens of circumstance (arising from the environment), practice (arising from peoples’ deliberate practices) and task (arising from the nature of the task being performed) accounted for 87% of dispute occurrences. The environment associated with the use of traditional lump sum contracting was found to be associated with 72% of the disputes. The practice of deliberately not adhering to policies, and procedures, undertaking design reviews and distributing tentative design documents contributed to the problems arising. The task of failing to detect errors and misinterpreting contract terms and conditions contributed to disputation. It is suggested that organizations need to fundamentally re-examine their work processes, policies and procedures as well as behaviors if disputes are to be reduced in construction.